Dyspnoe und Hautausschlag bei einem 49-jährigen Patienten = Dyspnea and skin rash in a 49-year-old male patient - El-Battrawy, Ibrahim; Ansari, Uzair; Behnes, Michael; Britsch, Simone; Jabbour, Claude; Fastner, Christian; Bill, Verena; Borggrefe, Martin; Akın, Ibrahim (Der Internist, 2017)
We report on the case of a 49-year-old man who presented with increasing dyspnea and a skin rash. The community-acquired pneumonia was initially treated with broad spectrum antibiotics. The patient’s respiratory condition rapidly worsened and the clinical picture of Waterhouse-Friderichsen syndrome developed with disseminated intravasal coagulopathy and necrosis of the toes. An infection with Capnocytophaga canimorsus, which had been caused by an initially unmentioned dog bite was confirmed. In view of the fulminant course and the high risk of operative treatment of the ubiquitous necroses in all limbs, a joint decision for deescalation of therapy was made together with relatives. The patient died 14 days after admission to hospital.